KEPUTUSAN LINDUNG NILAI DAN FAKTOR - FAKTOR YANG MEMPENGARUHI (Studi Empiris Pada Bank Konvensional yang Terdaftar di BEI Periode 2009 - 2013) - Adam Damanik, Hepdityo Rizki; Muharam, Harjum (Diponegoro Journal of Management, 2015)
Hedging is an alternative of risk management that aims to protect the assets of company from losses caused by the risk. Hedging using derivative instrument are commonly used by company. This study’s purpose is to analyze the influence of independent variables which include Debt to Equity Ratio, Growth Opportunity, Dividend Policy, Size, Liquidity, and Institutional Ownership on Hedging Decision. This study uses secondary data derived from the annual financial statements of 25 banking firms listed on Indonesian Stock Exchange the period 2009 to 2013. Data analysis using logistic regression test, by logistic regression analysis can be seen how the variables affect the probability of the company to hedge using derivative instruments. The results of this study found that Debt to Equity Ratio, Size, and Institutional Ownership have significant effect on Hedging Decision, whereas for the other variables did not influence Hedging Decision.